Research of flavour characteristics of beer with addition of pine extract - Penkina, Nataliya; Tatar, Larisa (Technology audit and production reserves, 2017)
The object of research is a light beer made according to the classical recipe (control) and beer «Emerald», made according to the classical recipe with the addition of pine extract. One of the most problematic places is that the expansion of the assortment of craft beer leads to the emergence of products with the addition of numerous synthetic components and flavors. The tasting method for evaluating the beverage is rather subjective, since it can’t fully characterize the effect of the qualitative composition and the quantitative content of the components of the raw materials used. Therefore, it is important to pay attention to the determination of the total amount of substances that are formed during the fermentation of beer wort and form the natural taste and aroma of the finished product. To carry out the experimental studies, malt barley light, hop granules, brewer’s yeast of bottom fermentation were used as the main raw material. Additional raw materials are selected pine needles. As methods of research, the method of high-performance gas chromatography and an adapted method for determining the number of fragrance are used. The concentration of flavoring substances is determined: beer control has 32 components, «Emerald» – 38, their calculations are carried out. It is determined that by-products of alcoholic fermentation refer to the factors that determine the taste and aroma of beer. To fully assess the weight of the aroma of the developed beer, the total content of the substances responsible for the flavor of the beverage is determined. It is found that the beer «Emerald» has a flavor number of 2740 ml of Na2S2O3/100 ml, control – 2170 ml of Na2S2O3/100 ml. This fully characterizes the effect on the finished product of the quantitative content of aroma-making additional raw materials. The positive effect of the developed beer «Emerald» is achieved due to: natural components, improved organoleptic parameters of the finished beverage, consumer’s curiosity to the new product. Also, the high antioxidant properties of additional raw materials contribute to reducing the negative impact of alcohol on the human body. Due to the partial replacement of hops, a lower price for the product was obtained in comparison with the analog product and a decrease in the negative influence of hop on the human body.